Therapeutic Applications of Solid Dispersions for Drugs and New Molecules: In Vitro and In Vivo Activities - Verônica da Silva Oliveira; Amanda Silva de Almeida; Ingrid da Silva Albuquerque; Fernanda Ílary Costa Duarte; Bárbara Cristina Silva Holanda Queiroz; Attilio Converti; Ádley Antonini Neves de Lima (Pharmaceutics, 2020)
This review aims to provide an overview of studies that address the use, in therapeutic applications, of solid dispersions (SDs) with biological activities in vitro and/or in vivo mainly made up of polymeric matrices, as well as to evaluate the bioactive activity of their constituents. This bibliographic survey shows that the development of solid dispersions provides benefits in the physicochemical properties of bioactive compounds, which lead to an increase in their biological potential. However, despite the reports found on solid dispersions, there is still a need for biological assay-based studies, mainly in vivo, to assist in the investigation and to devise new applications. Therefore, studies based on such an approach are of great importance to enhance and extend the use of solid dispersions in the most diverse therapeutic applications.